ENTRE PANOS E TRAMAS: A HIPERSSEXUALIZAÇÃO NO ESPORTE E OS DIZERES SOBRE O CORPO DA MULHER NO DISCURSO JORNALÍSTICO DIGITAL - MAIA, GABRIELLA MILDENBERGER (2023)
The history of women is engendered by several discursive memories that go back to the most primitive times. Her body has always been exalted through nudity, echoing discourses about femininity and aesthetic standards of beauty. In addition, the imaginary of a fragile and submissive subject helped to control even more the women's bodily practices. From the 20th century onwards, significant changes can be noticed in the positions exercised by this subject. However, in the management of Getúlio Vargas, president of Brazil between 1930 and 1954, an abyss still prevailed in relation to the education of men and women, especially to prevent sports practices that could, supposedly, masculinize bodies and threaten femininity. In 2021, three events reignited discourses on the sexualization of women's bodies in sport. The first was the 9th Artistic Gymnastics Championship, which took place in Basel, Switzerland, in April, when the German gymnast Sarah Voss took the initiative and wore a full body jumpsuit in her presentation on the ground as a form of protest against the sexualization in sport; the second occurred at the European Women's Beach Handball Championship, in July, when the Norwegian team was fined by the European Handball Federation for violating the rules by choosing to wear shorts instead of bikinis; the third was during the Tokyo Olympics, also in July, when the German gymnasts, encouraged by Sarah Voss's gesture, chose to wear full-length overalls instead of the traditional tights. What interests us in this work is to investigate which discourses erupted in the digital journalistic discourse about the woman's body in/from the field of sport, crystallizing or breaking with already stabilized meanings. Specifically, we seek: a) to understand the digital space as a place for the formulation and circulation of journalistic discourse; b) examine how women's clothing can function as an empowerment or submission device; c) analyze which memories erupt about the woman and her body in the journalistic discourse. The analytical gesture focused on two reports: one published on the BBC News Brasil website, released on April 25, 2021, and another on the Correio Braziliense website, on August 15, 2021. The research is supported by the Frank Discourse Analysis -Brazilian, which aims to understand the production processes of the senses.